rPbPga1 from Paracoccidioides brasiliensis Activates Mast Cells and Macrophages via NFkB. - Clarissa Xavier Resende Valim; Elaine Zayas Marcelino da Silva; Mariana Aprigio Assis; Fabricio Freitas Fernandes; Paulo Sergio Rodrigues Coelho; Constance Oliver; Maria Célia Jamur (Public Library of Science (PLoS), 2015)
BACKGROUND:The fungus Paracoccidioides brasiliensis is the leading etiological agent of paracoccidioidomycosis (PCM), a systemic granulomatous disease that typically affects the lungs. Cell wall components of P. brasiliensis interact with host cells and influence the pathogenesis of PCM. In yeast, many glycosylphosphatidylinositol (GPI)-anchored proteins are important in the initial contact with the host, mediating host-yeast interactions that culminate with the disease. PbPga1 is a GPI anchored protein located on the surface of the yeast P. brasiliensis that is recognized by sera from PCM patients. METHODOLOGY/PRINCIPAL FINDINGS:Endogenous PbPga1 was localized to the surface of P. brasiliensis yeast cells in the lungs of infected mice using a polyclonal anti-rPbPga1 antibody. Furthermore, macrophages stained with anti-CD38 were associated with P. brasiliensis containing granulomas. Additionally, rPbPga1 activated the transcription factor NFkB in the macrophage cell line Raw 264.7 Luc cells, containing the luciferase gene downstream of the NFkB promoter. After 24 h of incubation with rPbPga1, alveolar macrophages from BALB/c mice were stimulated to release TNF-α, IL-4 and NO. Mast cells, identified by toluidine blue staining, were also associated with P. brasiliensis containing granulomas. Co-culture of P. Brasiliensis yeast cells with RBL-2H3 mast cells induced morphological changes on the surface of the mast cells. Furthermore, RBL-2H3 mast cells were degranulated by P. brasiliensis yeast cells, but not by rPbPga1, as determined by the release of beta-hexosaminidase. However, RBL-2H3 cells activated by rPbPga1 released the inflammatory interleukin IL-6 and also activated the transcription factor NFkB in GFP-reporter mast cells. The transcription factor NFAT was not activated when the mast cells were incubated with rPbPga1. CONCLUSIONS/SIGNIFICANCE:The results indicate that PbPga1 may act as a modulator protein in PCM pathogenesis and serve as a useful target for additional studies on the pathogenesis of P. brasiliensis.